Validation of the Viral Load Testing Criteria – an algorithm for targeted viral load testing in HIV‐positive adults receiving antiretroviral therapy - Thorman, Johannes; Björkman, Per; Tesfaye, Fregenet; Jeylan, Asiya; Balcha, Taye Tolera; Reepalu, Anton (Tropical medicine & international health, 2019)
Objectives Restricted capacity for viral load (VL) testing is a major obstacle for antiretroviral therapy (ART) programmes in high‐burden regions. Algorithms for targeted VL testing could help allocate laboratory resources rationally. We validated the performance of the Viral Load Testing Criteria (VLTC), an algorithm with satisfactory performance in derivation (sensitivity 91%, specificity 43%). Methods HIV‐positive adults who had been receiving first‐line ART for ≥12 months at three Ethiopian public ART clinics were included. Healthcare providers collected data on variables of the VLTC: current CD4 count, mid‐upper arm circumference (MUAC) and self‐reported treatment interruption. VL testing was performed in parallel. Performance of the algorithm for identification of patients with VL ≥ 1000 copies/ml was evaluated. Results Of 562 patients (female 62%, median ART duration 92 months), 33 (6%) had VL ≥ 1000 copies/ml. Sensitivity for the VLTC was 85% (95% CI, 68–95), specificity 60% (95% CI, 55–64), positive predictive value 12% (95% CI, 10–14) and negative predictive value 98% (95% CI, 97–99). Use of the algorithm would reduce the number of VL tests required by 57%. Misclassification occurred in 5/33 (15%) of subjects with VL ≥ 1000 copies/ml. Conclusion In validation, the VLTC performed similarly well as derivation. Use of the VLTC may be considered for targeted VL testing for ART monitoring in high‐burden regions. Objectifs La capacité restreinte de mesure de la charge virale (CV) constitue un obstacle majeur pour les programmes de traitement antirétroviral (ART) dans les régions à prévalence élevée. Des algorithmes pour des tests ciblés de la CV pourraient aider à allouer les ressources de laboratoire de manière rationnelle. Nous avons validé la performance des critères de mesure de la charge virale (VLTC), un algorithme dont la performance de dérivation est satisfaisante (sensibilité de 91%, spécificité de 43%). Méthodes Des adultes VIH positifs qui recevaient un ART de première ligne depuis au moins 12 mois dans trois cliniques ART publiques éthiopiennes ont été inclus. Les prestataires de soins de santé ont collecté des données sur les variables des VLTC: nombre actuel de CD4, périmètre brachial et interruption de traitement auto‐déclarée. La mesure de la CV a été réalisée en parallèle. La performance de l'algorithme pour l'identification des patients avec une CV≥1000 copies/mL a été évaluée. Résultats Sur 562 patients (femmes 62%, durée médiane de l’ART 92 mois), 33 (6%) avaient une CV ≥1000 copies/mL. La sensibilité des VLTC était de 85% (IC95%: 68‐95), sa spécificité de 60% (IC95%: 55‐64), sa valeur prédictive positive de 12% (IC95%: 10‐14) et sa valeur prédictive négative de 98% (IC95%: 97‐99). L'utilisation de l'algorithme réduirait le nombre de tests de CV requis de 57%. Une mauvaise classification est survenue chez 5/33 (15%) des sujets avec CV ≥1000 copies/ml. Conclusion En validation, les VLTC ont obtenu une performance aussi bonne comme dérivation. L'utilisation des VLTC peut être envisagée pour des mesures ciblées de la CV dans le suivi des ART dans les régions à forte charge de morbidité.